Giant sumpweed (Cyclachaena xanthiifolia (Nutt.) Fresen.): seed stocks, seedling dynamics, methods control - O. Kurdiukova; O. Tyshchuk (Карантин і захист рослин)
Goal. To assess the degree of danger of contamination of the sowing layer and an increase in stocks of Giant sumpweed seeds in the soil, the timing and dynamics of seedlings emergence, to develop a control pathway aimed at their reduction.